DOES IT PAY TO BE TECHNICALLY EFFICIENT? EFFICIENCY AND PROFITABILITY IN INDONESIAN ISLAMIC RURAL BANKS WITH CONTROL VARIABLE MACRO ECONOMICS AND BANK CHARACTERISTICS - Wibowo, Febrian Wahyu; Sujono, Rusny Istiqomah; Layli, Meutia; Afifah, Afina Ayu (Al-Infaq: Jurnal Ekonomi Islam, 2022)
BPRS is part of the banking system which has become large enough for Indonesia's economy, which tend to have more actively market their products in traditional markets or in the village, from the results of these remittances bank profit or advantage. With pengefektifan in gathering together and channelling of funds then it will get the maximum profit. Therefore this research aims to analyze the effect of efficiency and profitability of the BPRS in Indonesia. This research analysis tools using a Random Effect Regression (GLS) and use the data panel the secondary data obtained from Bank Indonesia audit of financial reports to see the big profitability is influenced by efficiency. This research uses elements of the crosssectional reflected by different banks in Indonesia and time series element reflected in the period in the period 2010-2016 in Indonesia. The findings in this study said that influential positive Efficiency significantly to the level of profitability of the BPRS in Indonesia.